2018
DOI: 10.1051/0004-6361/201832635
|View full text |Cite
|
Sign up to set email alerts
|

First core properties: from low- to high-mass star formation

Abstract: Aims. In this study, the main goal is to understand the molecular cloud core collapse through the stages of first and second hydrostatic core formation. We investigate the properties of Larson's first and second cores following the evolution of the molecular cloud core until formation of Larson's cores. We expand these collapse studies for the first time to span a wide range of initial cloud masses from 0.5 to 100 M . Methods. Understanding the complexity of the numerous physical processes involved in the very… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 47 publications
4
53
0
Order By: Relevance
“…Many authors have since repeated and improved Larson's numerical experiments, but the mass of the first Larson core M 1LC is still found to be of the order 0.02 M and has proven to be very robust against variations in the equation of state and the properties of the surrounding envelop (e.g. Vaytet et al 2013;Krumholz 2017;Bhandare et al 2018;Lee & Hennebelle 2018b). When the second Larson core forms, it accretes the leftovers of the first Larson core on a very short timescale.…”
Section: The Mass Of the First Larson Corementioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have since repeated and improved Larson's numerical experiments, but the mass of the first Larson core M 1LC is still found to be of the order 0.02 M and has proven to be very robust against variations in the equation of state and the properties of the surrounding envelop (e.g. Vaytet et al 2013;Krumholz 2017;Bhandare et al 2018;Lee & Hennebelle 2018b). When the second Larson core forms, it accretes the leftovers of the first Larson core on a very short timescale.…”
Section: The Mass Of the First Larson Corementioning
confidence: 99%
“…New sinks are allowed to merge with another older sink only during a time scale t merge after their birth (Bleuler et al 2015). This time scale is associated with the first Larson core lifetime, and is usually chosen around 1000 yr, which corresponds to the dynamical time of the first Larson core (Bhandare et al 2018). During this time scale, we expect the first Larson core to still be gaseous and a collision with another core will lead to one protostar rather than a binary.…”
Section: Sink Particle Formationmentioning
confidence: 99%
“…First cores can have a variety of temperatures and radii, which largely depend on the initial conditions of the collapse and the age of the first core. For example, Bhandare et al (2018) showed that radii can vary from ∼1 to 10 au, and the first-core temperatures start at ∼10 K and rise to ∼2000 K before collapsing to a second (i.e., protostellar) core. The VANDAM survey observed Per-bolo-45 with the VLA in the B configuration only and had a sensitivity of ∼0.1 K at 8 mm.…”
Section: Per-bolo-45mentioning
confidence: 99%
“…This evolutionary picture is still currently the commonly admitted scenario for low-mass star formation. For massive star formation, recent work indicates that first cores may not have time to form because of the large accretion rates (Bhandare et al, 2018). Note that in the reminder of the section dedicated to second collapse, we mention only the work which is consistent with the Larson evolutionary picture, i.e., where the gas thermal and chemical budgets are taken into account, and we do not mention the work that has been done using an isothermal approximation.…”
Section: Historical Work and 1d Studiesmentioning
confidence: 99%
“…Modern studies began with the calculations performed in Masunaga and Inutsuka (2000) who incorporated a more accurate radiation transport scheme as well as a realistic gas equation of state which accounts for H 2 dissociation. Masunaga and Inutsuka (2000) integrated their models throughout the Class 0 and Class I phases up to an age of 1.3 × 10 5 yr. Nowadays, 1D models are still used either as a first step toward describing more accurately the physics of the protostellar collapse, e.g., with multigroup radiative transfer (Vaytet et al, 2013(Vaytet et al, , 2014 or with a view to provide quantitative predictions for the first and second Larson core properties (Vaytet and Haugbølle, 2017;Bhandare et al, 2018). These models are not pushed in time as far as the ones by Masunaga and Inutsuka (2000).…”
Section: Historical Work and 1d Studiesmentioning
confidence: 99%